58‐2: Distinguished Paper: Active Matrix QD‐LED with Top Emission Structure by UV Lithography for RGB Patterning. Issue 1 (25th September 2020) - Nakanishi, Yohei; Takeshita, Tomohiro; Qu, Yang; Imabayashi, Hiroki; Okamoto, Shota; Utsumi, Hisayuki; Kanehiro, Masayuki; Angioni, Enrico; Boardman, Edward A.; Hamilton, Iain; Zampetti, Andrea; Berryman-Bousquet, Valerie; et al.
Abstract : We have developed full colour top emitting quantum dot light emitting diode (QD‐LED) display driven by a 176 ppi active matrix of metal oxide thin film transistors. Red, green and blue (RGB) QD‐LED sub pixel emission layers are patterned by our original UV photolithography process and materials. We also demonstrate the potential to achieve high resolution such as 528 ppi using this process.